Drying dynamics of meat highlighting areas of relevance to dry‐aging of beef. Issue 6 (2nd October 2021) - Álvarez, Sara; Álvarez, Carlos; Hamill, Ruth; Mullen, Anne Maria; O'Neill, Eileen
Abstract: Drying of foods is a processing step, which has a variety of outcomes from improving shelf life and product stability, to reducing weight, or to achieving a targeted product eating quality. Drying is key step in the manufacturing of some dried meat products, such as jerky. It is also a major event that occurs when beef is dry‐aged, where beef is exposed to air under defined conditions for an extended aging period. Although the conditions typically used to produce dried meat products are significantly different from those that prevail during dry‐aging, both involve a gradual removal of water from muscle. As there is a paucity of research on the kinetics of the dehydration process occurring during dry‐aging of beef, this paper comprehensively reviews models used to describe drying kinetics in other beef products, in order to gain insights regarding the key factors that impact water removal from meat. Consideration is given as to how the specific conditions during dry‐aging such as air flows used (approximately 2 m/s), high air relative humidity, low temperature, and meat geometry will influence the kinetics of the drying. With regard to modeling, equations derived from Fick's second law of diffusion (e.g., thin‐layer models) have been used to describe the drying kinetics of small‐sized meat products. However, to apply Fick's law to dry‐aging, some different considerations may need to be evaluated such as: tridimensional geometry (i.e., whole muscle); uniform initial moisture content; isotropic diffusion; negligible shrinkage;and a combination of internal and external resistances.